مهارات التّواصل لدى أطفال اضطراب طيف التّوحّد (Journal of Hama University, 2025)
Autism spectrum disorder is a comprehensive developmental disorder that negatively affects many aspects of growth in children with autism spectrum disorder. Perhaps the most prominent effect of this disorder is the communication skills disorder, which manifests itself in the absence of verbal, nonverbal and social communication skills.Many studies on the treatment of children with autism, which aimed to develop their communication skills, have shown that training programs that adopted different strategies, whether based on peer modeling via video or direct live communication, contributed to the development of communication skills. To the best of the researcher's knowledge, the training programs followed in autism centers in Lebanon and Syria are limited to using live interaction with the autistic child, and this is confirmed by the researcher's field experience. There are also no studies in the Arab environment that have addressed the comparison between the peer modeling method through video and live interaction to develop verbal and non-verbal communication skills in autistic children. Therefore, we applied the current study with the aim of comparing these two methods with each other. The quasi-experimental research was applied at the Autism Center in Lattakia and the Waheet Al-Farah Center in Lebanon-Tripoli on a sample of 20 children, who were divided into two groups in each center. The researcher designed a representative video in which she used a healthy child to record the communication skills targeted in the current study. It was shown to half of the sample members and used live interaction with the other half of them for comparison.